Dampak Konten YouTube Livestream Marapthon Reza Arap terhadap Persepsi Penonton melalui Cultivation Theory - Muhammad Reza Akbar; Azwar Sutan Malaka; Kusumajanti (Jurnal Komunikasi dan Ilmu Sosial, 2026)
YouTube livestreaming content such as MARAPTHON from Reza Arap's ybrap channel has become a streaming phenomenon in Indonesia, attracting millions of viewers with its long-form, donation-based livestream format. This study uses a literature review to analyze how such content potentially shapes audience perceptions through Cultivation Theory, which posits that repeated media exposure creates a mainstream view of reality. The results suggest that MARAPTHON content can reinforce perceptions of interactive entertainment, online communities, and donation norms, with implications for the mainstream across various audience groups. The conclusion recommends further empirical research to gauge its long-term effects.